The Radical Enlightenment and Freemasonry: Where We Are Now - Jacob, Margaret (2013)
Sometimes updating the observations and conclusions achieved long ago is necessary, especially when new scholarship on the topic appears. In this article, recent works about the relationship between radical enlightenment and Freemasonry are discussed.